Assistance in Marketing Management and Packaging of Fried Gethuk Processed Food in Lebak Village, Jepara Regency - Rahmawati, Wahyuni; Ayu, Kiki Trisna; Iskak, Ahmad; Saefudin, Ahmad; Hudi (Talenta Publisher, 2021)
Dedication to the gethuk goreng Aida partner has the aim of solving partner problems, namely the management of this partner is still not solid because of the lack of knowledge about MSME management by business actors, this can be seen in the absence of spending notes, cash books, and stamps. For the packaging section, partners still need improvement in providing product labels because partner product labels do not attract consumers' attention to buy partner products. The solution to this partner problem is to improve the partner management system which includes online and offline partner marketing, as well as infrastructure management for service partners. The next goal is to improve the production label to make it more attractive. From these objectives, it can be obtained benefits for partners, namely increased monthly turnover because the number of consumer orders is influenced by solid management, and the number of consumers is also influenced by attractive packaging. The method of implementation in this service is observation, interview, and implementation. The approach is carried out by provisioning and mentoring after field observations are made. The data used in this community service are primary and secondary data, primary data is obtained from observation and provision of training aimed at developing the respondent's business and secondary data is obtained from literature studies, including from journals, the internet. The result of the 40 days of dedication is an increase in weekly sales in one month, and for the future partners can increase their sales again by maintaining the quality of partner products.